Diagnosis of Farmers' Sowing Practices for Cotton (Gossypium Hirsutum L.) to Improve Plant Density per Hectare in Mali - Sissoko, Sory; Dembele, Bandiougou; Maïga, Aliou D.; Dembele, Moussa; Rueff, Marine; Soumare, Mamy (European Journal of Applied Sciences, 2025)
In Mali, cotton production faces a number of constraints that partly limit its yield. The low planting density is the most significant of these constraints. The objective of the study is to identify practices that are more or less suitable for improving cotton planting density in the field. A quantitative and qualitative survey of current sowing densities on farms in Mali's cotton-producing zones was carried out among 300 farmers in 20 villages. Simple descriptive statistics, frequencies or percentages, and analyses of variance were applied to the data collected to determine means, significance of differences between means, and other parameters. The results showed low densities, with an average of 44,200 plants per hectare, well below the recommended density of 83,333 plants per hectare. The best practices identified included using recent generation seed (R1) (57,600 plants/ha), fungicide treatment of the seed before sowing (56,500 plants/ha), sowing after scraping the plot (54,500 plants/ha), and sowing with a drill (53,100 plants/ha). Low densities were recorded with the use of two types of mixed seed (delinted and undelinted) (25,600 plants/ha), the use of the old seed variety NTA 90-5 (25,600 plants/ha), and children removing seedlings (27,400 seedlings/ha). The results show that the low densities are linked more to practices than to the climatic conditions often mentioned.